Performance investigation of a loop heat pipe integrated with thermoelectric cooler under acceleration field. (October 2021) - Fang, Zhen; Xie, Yongqi; Xu, Yanmeng; Wu, Hongwei; Zhang, Hongxing; Han, Longzhu
Highlights: Operating performance of DCCLHP is studied experimentally under acceleration field. The effect of thermoelectric cooler (TEC) on operating performance are analyzed. The effect of acceleration magnitudes on operating performance of LHP is discussed. The effect of acceleration directions on operating performance is concluded. Abstract: This paper presents an experimental investigation on a novel dual compensation chamber loop heat pipe (DCCLHP) integrated with thermoelectric cooler (TEC) for improving the overall performance under various acceleration conditions. The operating characteristics of the DCCLHP with and without the assistance of TEC for configurations A and B are analyzed systematically under different acceleration magnitudes and heat loads. The heat load on the evaporator ranges from 25 W to 300 W and the power of the TEC is 10 W. The acceleration magnitude ranges from 5 g to 13 g. Experimental results show that: (i) the application of TEC is proved to improve the operating performance for the heat load not exceeding 150 W under configuration A and 100 W under configuration B; (ii) under configuration B, the increase of the acceleration normally leads to the increase of the operating temperature and the decrease of the thermal conductance. While it shows no obvious effect on the operating performance under configuration A for most cases. The maximum operating temperature and thermal conductance is 56.7 °C at 150 W under 13 g for configuration B, while 20.7 W/K at 150 W under 5 g for configuration A; (iii) temperature fluctuation occurs at 100 W under both 5 g and 7 g for configuration B, whereas there is no fluctuation under configuration A. The acceleration effect can change the vapor-liquid distribution in the loop and the external loop pressure drop, which will further change the operating performance along with the TEC effect. This research can provide valuable insight into the influence of TEC on DCCLHP under different acceleration field, which is of great significance for its practical application in mechanical and aerospace engineering.